The incidental finding of elevated anti GQ1B antibodies in a patient with selective small fiber neuropathy. Issue 1 (January 2019) - Favoni, V.; Liguori, R.; Incensi, A.; Fileccia, E.; Donadio, V.
Abstract : Small fiber neuropathy occurs in several autoimmune diseases and autoantibodies against neuronal proteins may play a role in SFN pathophysiology. 1−2 Antigangliosides antibodies anti-GQ1b have not previously associated to SFN. We describe a 45-year-old woman complaining of a two-year history of tingling and/or burning pain sensation in the arms and legs, with nocturnal exacerbation. The anamnesis revealed a ten-year history of an autoimmune disorder including HLA-B27 negative psoriatic arthritis, complement C3 deficiency membrano-proliferative glomerulonephritis and sicca syndrome. Neurological examination did not disclose ophthalmoplegia, signs of central nervous dysfunctions or peripheral large nerve fiber abnormalities. Laboratory screening disclosed IgM antiganglioside antibodies anti-GQ1b (high titer) and anti-GD1b (low titer). Skin biopsies from distal leg and thigh revealed decreased epidermal nerve fiber density, whereas autonomic innervation of dermal annexes was preserved. Motor and sensory nerve conduction studies were normal excluding a large nerve fiber involvement. SFN likely explained the sensory dysfunctions complained of by the patient. A trial with adalizumab resulted in long-term pain relief. This is the first report of SFN associated with antigangliosides antibodies anti-GQ1b. Further studies will clarify a possible pathogenetic role of these antibodies in SFN. Moreover, their recognition of in SFN may be an indicator of patients who would potentially benefit from immunotherapy.